Sosialisasi Penggunaan Software Vissim Untuk Menganalisis Dampak Pembangunan Gedung Terhadap Kinerja Lalu Lintas - Veronica Veronica; Abdullah Ade Suryobuwono; Aditya Nugroho; Dimas Nu’man Fadhil; Rizky Febriansyah (Institut Transportasi dan Logistik Trisakti, 2023)
The targets in this PkM activity are our partners, namely DTKJ, policy-making agencies and the public using transportation so that it can run more optimally. Transportation is a very important and strategic tool in accelerating the wheels of the economy, strengthening unity and integrity and affecting all aspects of national and state life. In Jakarta, the unresolved transportation problem is congestion, especially at certain points which are meeting centers from various directions, so it is very important to have signposted intersections to avoid conflicts that occur on the roads. Therefore, it is necessary to have a more in-depth study in determining the capacity of the road, the length of the vehicle queue, the estimated traffic volume, and the level of road service. Therefore, an assessment was carried out using the Vissim software where the assessment can be carried out with 3D simulation which will make it easier to analyze a road section and be able to find out the actual conditions that occur on that road segment. This PkM activity succeeded in introducing Socialization of the use of Vissim software which has not widely known by many people and providing an understanding of what Vissim simulation.